2022
DOI: 10.1017/s1930297500008895
|View full text |Cite
|
Sign up to set email alerts
|

Debiasing System 1: Training favours logical over stereotypical intuiting

Abstract: Whereas people’s reasoning is often biased by intuitive stereotypical associations, recent debiasing studies suggest that performance can be boosted by short training interventions that stress the underlying problem logic. The nature of this training effect remains unclear. Does training help participants correct erroneous stereotypical intuitions through deliberation? Or does it help them develop correct intuitions? We addressed this issue in four studies with base-rate neglect and conjunction fallacy problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
28
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 78 publications
9
28
1
Order By: Relevance
“…In sum, these results confirm that the training improved reasoning performance, as early as the initial ‘intuitive’ stage. In this study, we replicated the sound intuiting effect found in previous debiasing studies (e.g., Boissin et al, 2021 , 2022 ). In other words, after the training intervention, reasoners were able to intuit the correct solution strategy and typically no longer required to correct an initial ‘erroneous’ response through deliberation.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…In sum, these results confirm that the training improved reasoning performance, as early as the initial ‘intuitive’ stage. In this study, we replicated the sound intuiting effect found in previous debiasing studies (e.g., Boissin et al, 2021 , 2022 ). In other words, after the training intervention, reasoners were able to intuit the correct solution strategy and typically no longer required to correct an initial ‘erroneous’ response through deliberation.…”
Section: Resultssupporting
confidence: 89%
“…However, strictly speaking, participants who select the singular very unlikely option (e.g., ‘an Oscar winner’ in the above example) do not violate the critical conjunction rule. As Boissin et al ( 2022 ) mentioned, given that we are interested in learning effects, selection of the very unlikely option can be considered a correct response. Hence, we considered answers on which the conjunction fallacy is avoided (i.e., unlikely and very unlikely answers) as correct answers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations